Population ecology of a critically endangered gecko, endemic to north-eastern of Argentina - Courtis, Azul Celeste (2022)
Homonota taragui is an endemic gecko of the northeast of Argentina. We estimate demographic parameters: number of individuals by populations, sex and ontogenetic stage; sexual dimorphism; survival of this species; and describe the use of microhabitat and movement patterns. We measured 11 morphological variables, determined the sex and marked individually. We found bigger head width in males. Some factors contribute to the vulnerability of this species such as its constrained geographical distribution, use of the specific microhabitat and the isolation of their populations. We highlight demography studies as an essential data source for management and conservation of critically endangered species.